Reliability analysis of ready-mix concrete plants using MLE and power law process - Monika Saini; Ashish Kumar; Dinesh Kumar Saini (Discover Applied Sciences)
Abstract The aim of the present study is to analyze the reliability measures of ready-mix concrete (RMC) plants using failure data collected from three different plants. RMC plant is a very complex structure involving five subsystems in series configuration. The major challenge faced during reliability investigation is the availability of sufficient data. To address this issue, here, the meta-analysis test is opted to merge the failure data of various plants. The parameter estimation of well-known distribution performed on pooled failure data utilizing MINITAB software. The descriptive statistics, trend and serial correlation of TBF, U-statistic and parameters estimation performed for all subsystems. The maximum likelihood and power law process used for estimation of the parameters of subsystems. The analysis of ready-mix concrete mixture plant data shows that Weibull distribution is the best-fitted distribution. This study offers significant insights to carry out the reliability investigation of RMC plants as well as very little work reported on effectiveness and reliability of such plants. It may be treated as a resource for improving the design and performance of plants by system designers.